Analysis on the Static Performance of a New Type of Large-Span Fabricated Grid-Plate Ribbed Composite Floor Structure. Issue 1 (February 2020) - Liu, Kai; Zhao, Xueying; Wu, Xuewen; Yi, Shuai; Zhou, Yan
Abstract: A new type of large-span fabricated grid-plate ribbed composite floor structure is proposed basis on fabricated steel-concrete composite structure. The new structure consists of four sides of rib, bottom slab and internal concrete block. In this paper, the static performance of the new structure is analysed by the finite element method and compared with the combined open-web sandwich plate structure. The analysis results show that the new type floor can reach 1/30-1/35 of the span. Under the same span, mesh size and load, compared with the existing combined open-web sandwich plate floor, the new type floor has large stiffness, small structure height, light weight, and reduce concrete and steel consumption by 77.6% and 7.3%, respectively. The structure is safe, reliable and has good economic benefits.